THE BELT AND ROAD INITIATIVE AND THE MEGA INFRASTRUCTURE INVESTMENTS IN AFRICA - Bonacina, Amabilly; Gazibo, Mamoudou (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
This article seeks to analyze the Sino-African relations and in particular the Belt and Road Initiative investments through the study of deviant cases. Using the cases of interrupted cooperation agreements in Sierra Leone and Tanzania under the initiative, this article argues that the interruption is caused mainly by the nature of the projects which make them vulnerable to changes in domestic politics. To explain this, we propose the concept of presidential megaprojects.